Internet connectivity disruption in Egypt (Egypt) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Egypt. Data sourced from IODA.
Network Disruption Incident ID: EG-2026-0206. Severity: critical. Confidence: 65%